PIDDosome Expression and the Role of Caspase-2 Activation for Chemotherapy-Induced Apoptosis in RCCs - Sebastian Heikaus; Igor Pejin; Helmut Erich Gabbert; Uwe Ramp; Csaba Mahotka (Cellular Oncology)
Background: The importance of caspase-2 activation for mediating apoptosis in cancer is not clear and seems to differ between different tumour types. Furthermore, only few data have been obtained concerning the expression of caspase-2, which can be alternatively spliced into caspase-2L and caspase-2S, and the other PIDDosome members PIDD and RAIDD in human tumours in vivo. We, therefore, investigated their expression in renal cell carcinomas (RCCs) of the clear cell type in vivo and analysed the role of caspase-2 in chemotherapy-induced apoptosis in RCCs in vitro.